The Integration of Religious Literacy in Enhancing the Pancasila Student Profile - Ramli, Rosmiati; Maswati; Sumiati AS (Pascasarjana Universitas KH. Abdul Chalim, 2025)
The Pancasila Student Profile represents a concrete manifestation of the national education goals, serving as a fundamental reference in shaping educational policies—including the crucial area of religious literacy. In reality, Indonesia continues to face issues such as bullying, child sexual abuse, and other incidents that highlight the urgent need for character reinforcement. This study aims to (i) identify the influence of religious literacy on the reinforcement of the Pancasila Student Profile (P5), (ii) map the dimensions and aspects integrated within religious literacy, and (iii) explore the integration patterns of religious literacy in strengthening P5. A mixed-methods approach was employed, combining both quantitative and qualitative procedures. The findings reveal three key points: First. At the same time, several indicators of religious literacy were statistically insignificant when analyzed individually; the variable significantly influences the reinforcement of P5. Second, the dimensions of the Pancasila Student Profile were further broken down into practical indicators for integration purposes. Third, the integration strategies were implemented through co-curricular, intra-curricular, and extracurricular activities using a multiliteracy approach. This study contributes to the reinforcement of the Pancasila Student Profile, aiming to cultivate students who are faithful, pious, and morally upright while also demonstrating global diversity, collaboration, independence, creativity, and critical thinking.